Pengaruh Self-Efficacy, Tolerance for Risk, dan Kebebasan dalam Bekerja terhadap Minat Entrepreneurship Mahasiswa Universitas Negeri Padang - Dara Putri Andini; Yunita Engriani (Jurnal Kajian Manajemen dan Wirausaha, 2019)
This research aims to analyze: (1) The influence of self-efficacy toward Entrepreneurial interest on students of Padang State University (2) The influence of tolerance for risk toward Entrepreneurial interest on students of Padang State University (3) The influence of work freedom toward Entreprenurial interest on students of Padang State University. This type of research is causative research. The population in this study were all active students of Padang State University. In this study the number of samples was determined using the Cochran formula sample obtained 100 people taken using purporsive sampling that the sample is chosen by several consideration according to its proportions and the chances are that each member of the population will be the same sample. This study was analyzed by multiple regression analysis using the SPSS version 25 program.Regarding the causal model proposed, the data confirm the relationship set out in the hypothesis. It can therefore be stated that (1) Self-Efficacy has a positive and significant effect on Entrepreneurial Interest on student of Padang State University  (2) Tolerance for Risk Support has a positive and significant effect on Entrepreneurial Interest on student of Padang State University (3) Work Freedomhas no significant effect on Entrepreneurial Interest on student of Padang State University. This analysis highlights the positive influences self-efficacy and tolerance for risk towards Entrepreneurial interest. However,the interest in entrepreneurship viewed form work freedom was of no significant effect. Keywords: Entrepreneurial Interest, Self-Efficacy, Tolerance for Risk, Work Freedom.